Autorzy:Drążek Anna, Duvnjak Ewa, Kokiernak-Jurkiewicz Ewa
Wydawnictwo:WSiP
Rok wydania:2016
Po uproszczeniu wyrażenie (-2√5a²+4√20a²-8√45)∙(-√1/5)4.63 gwiazdek na podstawie 8 opinii

Po uproszczeniu wyrażenie (-2√5a²+4√20a²-8√45)∙(-√1/5)

7Zadanie
8Zadanie
9Zadanie
10Zadanie
11Zadanie
12Zadanie
12Zadanie

`(-2sqrt5a^2+4sqrt20a^2-8sqrt45)*(-sqrt(1/5)a)-[-(-3a^2-6)*a]=`

`=2sqrt(5*1/5)a^3-4sqrt(20*1/5)a^3+8asqrt(45*1/5)-[-(-3a^3-6a)]=`

`=2sqrt1a^3-4sqrt4a^3+8sqrt9a-[3a^3+6a]=2a^3-4*2a^3+8*3a-3a^3-6a=`

`=2a^3-8a^3+24a-3a^3-6a=-9a^3+18a=3a(-3a^2+6)=3a(6-3a^2)=9a(2-a^2)=-9a(a^2-2)`